2006
DOI: 10.1002/cncr.22063
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of irinotecan plus cisplatin for patients with advanced stage IIIB or IV NSCLC previously treated with nonplatinum‐based chemotherapy

Abstract: BACKGROUND.Irinotecan (I) and cisplatin (P) are active chemotherapy agents with clinical synergy in non–small‐cell lung cancer (NSCLC). We evaluated the efficacy of IP regimen as a salvage treatment of patients with NSCLC that progressed after nonplatinum‐containing regimen(s).METHODS.Eligibility required histologically confirmed NSCLC, bidimensionally measurable disease, ECOG PS 0‐2, and progressive disease after nonplatinum‐based chemotherapy. Treatment consisted of I (65 mg/m2) and P (30 mg/m2) i.v. on Days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Human clinical studies have shown that combination treatment with irinotecan and cisplatin is efficacious in a wide range of cancer types including SCLC (9)(10)(11)(24)(25)(26), NSCLC (27)(28)(29), ovarian cancer (30), upper gastrointestinal cancers (31)(32)(33)(34)(35), and other less prevalent tumor types (36)(37)(38). Based on phase III randomized trials, this combination remains a prospective treatment for extensive-stage SCLC, with response and survival end points comparable to that of etoposide/cisplatin in the presence of reduced myelosupression.…”
Section: Discussionmentioning
confidence: 99%
“…Human clinical studies have shown that combination treatment with irinotecan and cisplatin is efficacious in a wide range of cancer types including SCLC (9)(10)(11)(24)(25)(26), NSCLC (27)(28)(29), ovarian cancer (30), upper gastrointestinal cancers (31)(32)(33)(34)(35), and other less prevalent tumor types (36)(37)(38). Based on phase III randomized trials, this combination remains a prospective treatment for extensive-stage SCLC, with response and survival end points comparable to that of etoposide/cisplatin in the presence of reduced myelosupression.…”
Section: Discussionmentioning
confidence: 99%